Linking Knowledge Search to Innovation Performance in Culinary SMES Sector: The Mediating Role of Digital Orientation - Ilhami, Susanti Dwi; Damayanti, Damayanti (Penerbit Goodwood, 2024)
Purpose: The purpose for this research is to explore the role of digital orientation in moderating the effect of knowledge search on innovation performance in culinary SMEs in Rembang Regency. Methodology: The type of research is quantitative using an explanatory research approach. The number of research samples is 82 culinary SMEs in Rembang Regency by using the purposive sampling method. Results: The research findings show that knowledge search has a significant effect on innovation performance. However, digital orientation cannot moderate the effect of knowledge search on innovation performance. Limitation: The use of limited sampling only in the Rembang regency so the findings cannot be generalized. In addition, the number of samples used in the research was too small therefore the scope of the research was limited. In this study, the research variables in the model only include 3 variables so that the research model is limited. Contribution: Based on the results of this research, culinary SMEs must improve their knowledge search capabilities therefore the innovation can be created optimally and also the implications of knowledge search can build a knowledge base for SMEs. In addition, these results can also be used for future research using the same research model.